A NOVEL METHOD OF THE HYDRIDE SEPARATION FOR THE DETERMINATION OF ARSENIC AND ANTIMONY BY AAS - Ganden Supriyanto; Jürgen Simon (Indonesian Journal of Chemistry, 2006)
A novel method is proposed for the hydride separation when determinining of arsenic and antimony by AAS. A chromatomembrane cell was used as preconcentration-, extraction- and separation-manifold instead of the U-tube phase separator, which is normally fitted in continuous flow vapour systems generating conventionaly the hydrides. The absorbances of the hydrides produced were measured by an atomic absorption spectrophotometer at 193.7 nm and 217.6 nm. Under optimized analytical conditions, the calibration plot for arsenic was linear from 50 to 500 ng.mL-1 (r2 = 0.9982). The precision for three subsequent measurements of 500 ng.mL-1 arsenic gave rise to a relative standard deviation of 0.4%. The detection limit was 15 ng.mL-1, which is much lower compared with that of the conventional hydride system (2000 ng.mL-1). A similar result was observed in case of antimony: the detection limit was 8 ng.mL-1 when the proposed method was applied. Consequently, the sensitivity of the novel method surpasses systems with conventional hydride generation, i.e. the precision and the acuracy increase whereas the standard deviation and the detection limit decrease. The proposed method was applied in pharmacheutial analysis and the certified As-content of a commercial product was very sufficiently confirmed.